The balancing of creditor interests in business rescue provisions of the Companies Act 2008 - Buba, Zolani P (Department of Commercial Law, 2018)
The integrated global economy has presented challenges as well as opportunities for companies and their surrounding communities. This has resulted in many jurisdictions having to re-evaluate the question of company failure and how best to deal with it. The South African context has seen the enactment of a new Companies Act, ushering in a rescue regime which evidences a significant departure from its predecessor; judicial management. Contained within Chapter 6 of the Companies Act of 2008, business rescue adopts a fresh approach to company resuscitation. With relatively easy access to the procedure, business rescue caters for the restructure of the business, debt or its equity to ensure either a return to solvency or a better return to creditors than in liquidation. The new regime is further underpinned by the 2008 Act purpose provision, which envisages an efficient business rescue procedure and further mandates that the resolution of financial distress be conducted in a manner that balances the rights and interests of all relevant stakeholders. It is in this light, that this study explores the interplay between section 7(k) and Chapter 6 of the new Act. Specifically, the work sets out to critique the manner in which our new business rescue regime balances competing stakeholder interests in its provisions and investigates whether current provisions provide an adequate framework for this to be done in a manner that enhances the regime's ability to return a financially distressed company to a position of solvency, as a primary objective. After discussing the previous judicial management regime and exploring the mechanics of Chapter 6, a comparative study of similar procedures in the United Kingdom and the United States is undertaken. The study further identifies a number of weaknesses and makes recommendation for improvement.